2015 3rd IEEE International Conference on Mobile Cloud Computing, Services, and Engineering 2015
DOI: 10.1109/mobilecloud.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Cloudlet Mesh for Securing Mobile Clouds from Intrusions and Network Attacks

Abstract: This paper presents a new cloudlet mesh architecture for security enforcement to establish trusted mobile cloud computing. The cloudlet mesh is WiFi-or mobile-connected to the Internet. This security framework establishes a cybertrust shield to fight against intrusions to distance clouds, prevent spam/virus/worm attacks on mobile cloud resources, and stop unauthorized access of shared datasets in offloading the cloud. We have specified a sequence of authentication, authorization, and encryption protocols for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The data stored on the cloud are safeguarded from illegal access by the proposed protocol safeguard. Moreover, Shi et al [10] proposed a new cloudlet architecture for security enforcement. The new architecture was established to enforce security by specifying authentication, encryption, and authorization for trusted mobile cloud computing.…”
Section: Related Workmentioning
confidence: 99%
“…The data stored on the cloud are safeguarded from illegal access by the proposed protocol safeguard. Moreover, Shi et al [10] proposed a new cloudlet architecture for security enforcement. The new architecture was established to enforce security by specifying authentication, encryption, and authorization for trusted mobile cloud computing.…”
Section: Related Workmentioning
confidence: 99%
“…Prospective issues diminished with the deployment of fog computing [14] that are authentication, intrusion attack, security, and privacy. A designed work distributes the cloudlets as a mesh based intrusion recognition system for security of micro clouds (fog nodes) from interferences and network attacks [53]. Previously predicted ideas [13] about security issues that are currently related to a VM based environment might create probable security anxiety at fog devices.…”
Section: Security and Privacymentioning
confidence: 99%
“…There are some studies related to intrusion detection in FC/MEC [5,15,16]. The security of edge computing has previously been reviewed [5], and the author suggested that FC/MEC is a paradigm of edge computing.…”
Section: Related Workmentioning
confidence: 99%
“…It has been noted that an IDS can be deployed on the fog node/MEC host side (host-side detection) or fog network/MEC network side (network-side detection) to monitor host-side intrusions or network-side attacks [15]. A new cloudlet mesh security architecture was proposed based on cloudlets [16], and this architecture is used to protect the mobile cloud network. If cloudlet servers are treated as fog nodes/MEC hosts, then such architecture constitutes a host-side IDS.…”
Section: Related Workmentioning
confidence: 99%